2011
DOI: 10.1039/c1cp20671k
|View full text |Cite
|
Sign up to set email alerts
|

Micro/nanoscale hierarchical structured ZnO mesh film for separation of water and oil

Abstract: Oil contaminated water is a common problem in the world, thus to effectively separate water and oil is an urgent task for us to resolve. By control of surface wettability of a solid substrate, both superhydrophobicity and superoleophilicity on a film can be realized, which is necessary for water and oil separation. Here we report a stable superhydrophobic and superoleophilic ZnO-coated stainless steel mesh film with special hierarchical micro/nanostructures that can be used to separate a water and oil mixture … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
147
0
1

Year Published

2012
2012
2017
2017

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 197 publications
(148 citation statements)
references
References 43 publications
0
147
0
1
Order By: Relevance
“…Membranes are typically classified as either hydrophobic or hydrophilic [3][4][5][6][7][8][9][10] . Their wettability by oil is often not specified because, in most cases, such membranes are oleophilic, that is, their contact angle with oil is < 90°.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Membranes are typically classified as either hydrophobic or hydrophilic [3][4][5][6][7][8][9][10] . Their wettability by oil is often not specified because, in most cases, such membranes are oleophilic, that is, their contact angle with oil is < 90°.…”
mentioning
confidence: 99%
“…Their wettability by oil is often not specified because, in most cases, such membranes are oleophilic, that is, their contact angle with oil is < 90°. Hydrophobic (or superhydrophobic [9][10][11] ) and oleophilic membranes are typically used in energyintensive cross-flow filtration systems 3,6,7 because they are unsuitable for gravity-driven oil-water separation. This is because water naturally settles below oil and against the membrane owing to its higher density, forming a barrier layer that prevents oil permeation.…”
mentioning
confidence: 99%
“…[135,136] The liquid permeability and repellency are crucial to control the flow by the electrostatic potential. Tabassian et al reported electric-field-induced wetting of nickel meshes coated by graphene for use as flow control devices (Figure 9).…”
Section: Electric-field-induced Selective Permeation For Separationmentioning
confidence: 99%
“…Therefore, the development of advanced oil/water separation materials that can selectively absorb oil (or water) while completely repelling water (or oil) is highly desirable. 21,22 Recently, some other materials with special wettability have been also fabricated for oil/water separation [23][24][25][26][27][28][29] and the related review has been reported. 30 Herein, we only focus on the polyurethane-based materials for oil/water separation.…”
Section: Introductionmentioning
confidence: 99%